Sanksi Kebiri dalam Perspektif Penologi - Candra, Marli; Rifqi, M. Jazil (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
The paper aims to examine the philosophy of punishment which is the basis for determining castration as a sanction or a form of treatment determined by the government. This paper puts forward a normative analytical approach to castration as a product of the law, strengthened by a comparative approach to the philosophy of punishment. The results illustrate that castration is an emotional expression of society towards the rise of sexual violence cases against children, likewise, as an effort to prevent it by paralyzing the ability of biological desire. Apart from the two supporting arguments, the reason for establishing castration as an additional punishment cannot be proven based on the deterrent effect, benefits and rehabilitative impact of castration. This paper also supports castration as a crime and not a treatment.